2019
DOI: 10.5435/jaaosglobal-d-19-00137
|View full text |Cite
|
Sign up to set email alerts
|

Narcotic-Free, Over-the-Counter Pain Management After Wide-Awake Hand Surgery

Abstract: Introduction:Prescribing opioids for postoperative pain has increased steadily, and hand surgery has been no exception. Current hand surgery literature does not describe the efficacy of pain self-management postoperatively. The purpose of this study is to describe our experience with over-the-counter (OTC), narcotic-free, postoperative pain management.Methods:We have done a retrospective chart review at an academic tertiary-care facility. Patients who underwent soft-tissue hand surgery in an office-based proce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(12 citation statements)
references
References 20 publications
0
12
0
Order By: Relevance
“… 2 , 11 , 12 Several studies were conducted to assess opioid consumption for tier 1 hand procedures. 2 , 4 , 5 , 6 , 9 , 10 , 11 , 15 , 16 , 17 Despite the opioid crisis, satisfaction remains a competing priority, and at times, it may be at odds with new prescribing protocols. 18 Our findings suggest that high levels of pain control and satisfaction can be achieved by adhering to a postoperative pain protocol.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“… 2 , 11 , 12 Several studies were conducted to assess opioid consumption for tier 1 hand procedures. 2 , 4 , 5 , 6 , 9 , 10 , 11 , 15 , 16 , 17 Despite the opioid crisis, satisfaction remains a competing priority, and at times, it may be at odds with new prescribing protocols. 18 Our findings suggest that high levels of pain control and satisfaction can be achieved by adhering to a postoperative pain protocol.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies conducted recently showed that implementing a prescribing protocol markedly decreased opioid use after common hand surgery. 4 , 6 , 10 , 16 , 17 , 21 Ilyas et al 4 conducted a randomized controlled trial on opioids versus nonsteroidal anti-inflammatory drugs for pain management after CTR. High satisfaction was achieved regardless of pill type, which indicates that pain relief can be achieved without opioids after surgery.…”
Section: Discussionmentioning
confidence: 99%
“…23 Selection bias and small patient numbers may leave surgeons with uncertainty when applied to all patients and all conditions. 6,26 Guidelines for multimodality therapy can also prove overly complex to implement in daily practice. 9,19,20,[29][30][31][32] An important component of multimodality approaches is setting the foundation for subsequent prescribing at the time of surgery.…”
Section: (Continued)mentioning
confidence: 99%
“…16-22 Nonopioid medications have demonstrated equal or greater efficacy in managing postoperative pain compared to opioids. 23-28 Guidelines instruct the use of multiple modalities employed simultaneously to control pain, with an emphasis on reducing the contribution from opioids. 29-33…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation